Evaluasi Kompetensi Inti Guru Pendidikan Agama Islam: Studi di Dinas Pendidikan Kabupaten Sumedang - Indah Pratiwi, Rizky; Syahidin; Firmansyah, Mokhammad Iman (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to reveal the quality of Islamic Religious Education Teachers at the elementary and junior high school levels under the auspices of the Sumedang Regency Education Office, West Java, Indonesia. Using a mixed-method approach and data collection techniques such as in-depth interviews and questionnaires analyzed using NVivo software, it was found that the competencies of Islamic Religious Education teachers do not yet fully meet the expected standards. The research findings identified five main forms of competencies: personality, pedagogical, professional, social, and spiritual, with several aspects within each dimension that still need improvement. Exemplary behavior, innovative teaching methods, learning motivation, communication skills, and religious understanding emerged as the primary areas of weakness identified. This study recommends the need for more contextual and sustainable competency development strategies to enhance the overall quality of Islamic Religious Education teachers in line with contemporary challenges and the needs of students.